(untitled) (Education in the 21st Century, 2023)
The purpose of the research is to analyze the nature and role of terminological and nomenclature units in the system of subject knowledge of future biology teachers, which is realized by solving such tasks: 1) to find out the essence and correlation of terminology / terminology and nomenclature system (biological binary nomenclature); 2) to develop a system of terminology and biological nomenclature processing using the course «Latin. Botanical terminology». The research methodology is based on theoretical methods: analysis and systematization of psychological-pedagogical and biological literature in order to determine the state and theoretical substantiation of the problem of formation of professional-terminological competence of future biology teacher. The scientific novelty of the article consists in an identify the interconnections of the nominative and terminological systems as the basis of the professional and terminological competence of the future biology teacher. Conclusions. The basis of professional and terminological competence of future biology teacher is mastering the term system and biological nomenclature. The unit of the termosystem is a term denoting a certain abstract concept and categories; the unit of nomenclature is nomen, special terms-names denoting single, specific concepts. A nomenclature is examined as constituent part of termsystem, or an intermediate between terms and proper names. A biological nomenclature is presented by nomens (specific binomens) that comply with the stages of notional division of the world organic system on taxones. A nomenclature provides the unambiguity of nomens in biological researches. We adhere to the idea, that a nomenclature is specific part of biological terminology. General for terminology and nomenclature is terminoelements. The purpose of special course"Latin. Botanical terminology" is harnessing of terminoelements. Based on the specificity of the study of Latin as the basis of biological terminology, particular attention is paid to the terminological meaning of words, the study of Greek-Latin terminology, as well as the study of etymology and semantics of biological terms. An indicative subject matter of the special course is presented. It’s include the study of the history of biological terminology and nomenclature; principles of construction of phytonomens; scientific binary nomenclature and international nomenclature code.